Quantitative analysis of topical treatments in atopic dermatitis: unexpectedly low use of emollients and strong correlation of topical corticosteroid use both with depression and concurrent asthma. (15th September 2019) - Choi, J.Y.; Dawe, R.; Ibbotson, S.; Fleming, C.; Doney, A.; Foerster, J.
Summary: Background: Despite decades of use, the actual amounts of topical corticosteroids (TCS) and emollients used in moderate‐to‐severe atopic dermatitis (AD) under real‐world conditions are unknown. Thus, it remains unclear whether inadequate use is widespread. Objectives: To quantify the use of TCS and emollients in moderate‐to‐severe AD. Methods: Double‐blinded drug prescribing was recorded prospectively at the point of drug dispensing within a catchment area of approximately 450 000 people over a 31‐year period in a population‐based cohort marked by failure of disease control in primary care ( n = 844). For each patient, prescribing was recorded over a 12‐month period in order to minimize fluctuations. Results: This approach resulted in a near‐complete dataset, which was essentially free of reporting bias and recording bias. Atopic comorbidities matched expected frequencies. Median use of TCS was statistically significantly higher in juvenile patients (age < 16 years) compared with adult patients (49·2 vs. 38·1 g per month), in male vs. female patients (46·8 vs. 29·7 g per month) and in patients receiving concurrent asthma treatment (40·4 vs. 26·7 g per month). TCS use was strongly associated with antidepressant treatment. Emollient use was unexpectedly low with a median of 9·6 g per day (range 1·4–30·1). Results were replicated in an independent validation cohort. Conclusions: Deficient use of emollients may be a factor contributing to AD severity. Our analysis showed that the use of TCS does not exceed current guidelines. Accurate quantification of topical treatments provides a widely accessible strategy to measure the real‐world impact of novel AD treatments. What's already known about this topic? Both emollient and topical corticosteroid (TCS) use have been a mainstay of atopic dermatitis (AD) treatment for over 60 years. The actual quantities used by patients under real‐world conditions are unknown. What does this study add? The real‐world use of emollients is fourfold lower than the amount recommended in current guidelines. Underuse of emollients may be a significant factor in disease exacerbation. The use of TCS is significantly higher in male patients and is higher in patients with AD who also have asthma. The use of TCS is strongly associated with concurrent antidepressant treatment. Abstract : Linked Comment: Strowd and Feldman. Br J Dermatol 2020; 182 :836–837. Plain language summary available online